(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe the clinical features of acute rhinosinusitis in children; to evaluate bacteriological characteristics in children with acute rhinosinusitis. Research objects and methods: Cross-sectional descriptive study of 42 children diagnosed with acute rhinosinusitis according to the EPOS 2020 from March 2022 to September 2022. Results: 95.2% of pediatric patients have symptoms of runny nose. Most patients present with edema of the nasal mucosa, purulent fluid on the floor of the nose, and purulent fluid in the middle nasal cavity. Among them, white/yellow/green thick pus in the nostrils accounts for the highest proportion, and in some cases there is cloudy mucus pus in the nostrils. The rate of bacterial growth accounted for 54.8%. All specimens had only 1 strain of bacteria. The 3 most common bacterial species are: S. pneumonia, H. influenza and M. catarrhalis with a rate of 65.2% respectively; 17.4% and 13%. With the antibiotic Amoxicillin + Clavulanic Acid, bacteria have a fairly high sensitivity of 75-100%. Cefuroxime and Trimethoprim + Sulfamethoxazole have low sensitivity in most bacterial groups. Conclusion: Culturing and identifying bacteria in acute rhinosinusitis in children helps doctors guide the use of appropriate antibiotics for treatment.